Volume 5: 27th Biennial Mechanisms and Robotics Conference 2002
DOI: 10.1115/detc2002/mech-34205
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Compliant Mechanisms

Abstract: A systematic method for dynamic analysis of compliant mechanisms is presented including basic formulations for natural frequencies, modes, dynamic response, and frequency characteristics. Methods for design sensitivity analysis are developed to investigate the effect of various design parameters on the dynamic performance of compliant mechanisms. A micro compliant stroke amplifier mechanism, for MEMS actuator application, is presented as a design example to demonstrate significant differences between static an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Lin et al [14] approached the dynamic response of flexure-based micro-positioning stages by transforming the infinite degree-offreedom system into a lumped parameter model with a finite number of degrees of freedom. Li and Kota [15] presented a dynamic analysis of a microcompliant stroke amplifier mechanism. The results demonstrated that there were significant differences between static and dynamic performances for the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [14] approached the dynamic response of flexure-based micro-positioning stages by transforming the infinite degree-offreedom system into a lumped parameter model with a finite number of degrees of freedom. Li and Kota [15] presented a dynamic analysis of a microcompliant stroke amplifier mechanism. The results demonstrated that there were significant differences between static and dynamic performances for the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Designing CMs for specific applications can be a complex problem with many considerations. The basic trade-off is between the flexibility to achieve deformed motion and the rigidity to sustain external load [5]. The pseudo-rigid-body-model (PRBM) technique is a design tool that approximates the force-deflection relationships of CMs by assigning a rigid-body, lumped compliance counterpart to every flexible segment comprising the mechanism [2].…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [23] proposed a new method to establish PRB models for beambased compliant mechanism, where the behavior of parallel linear spring stage beams are imitated by a rigid bar with two pin-joints. Li and Kota [24] studied dynamics analysis of compliant mechanisms including natural frequencies, modes, dynamic response, and frequency characteristics, by using the finite element method. Zhao et al [25] developed a dynamic model based on Lagrange equation for a compliant linear-motion mechanism, then investigated the effect of material properties, shape parameters, and geometric parameters on natural frequency for providing quantitative insight to designers.…”
Section: Introductionmentioning
confidence: 99%